Intermittent inotropic support with levosimendan in advanced heart failure as destination therapy: The LEVO‐D registry. (19th January 2023) - Dobarro, David; Donoso‐Trenado, Víctor; Solé‐González, Eduard; Moliner‐Abós, Carlos; Garcia‐Pinilla, José Manuel; Lopez‐Fernandez, Silvia; Ruiz‐Bustillo, Sonia; Diez‐Lopez, Carles; Castrodeza, Javier; Méndez‐Fernández, Ana B.; Vaqueriza‐Cubillo, David; Cobo‐Marcos, Marta; et al.
Abstract: Aim: Patients with advanced heart failure (AHF) who are not candidates to advanced therapies have poor prognosis. Some trials have shown that intermittent levosimendan can reduce HF hospitalizations in AHF in the short term. In this real‐life registry, we describe the patterns of use, safety and factors related to the response to intermittent levosimendan infusions in AHF patients not candidates to advanced therapies. Methods and results: Multicentre retrospective study of patients diagnosed with advanced heart failure, not HT or LVAD candidates. Patients needed to be on the optimal medical therapy according to their treating physician. Patients with de novo heart failure or who underwent any procedure that could improve prognosis were not included in the registry. Four hundred three patients were included; 77.9% needed at least one admission the year before levosimendan was first administered because of heart failure. Death rate at 1 year was 26.8% and median survival was 24.7 [95% CI: 20.4–26.9] months, and 43.7% of patients fulfilled the criteria for being considered a responder lo levosimendan (no death, heart failure admission or unplanned HF visit at 1 year after first levosimendan administration). Compared with the year before there was a significant reduction in HF admissions (38.7% vs. 77.9%; P  < 0.0001), unplanned HF visits (22.7% vs. 43.7%; P  < 0.0001) or the combined event including deaths (56.3% vs. 81.4%; P  < 0.0001) during the year after. We created a score that helps predicting the responder status at 1 year after levosimendan, resulting in a score summatory of five variables: TEER (+2), treatment with beta‐blockers (+1.5), Haemoglobin >12 g/dL (+1.5), amiodarone use (−1.5) HF visit 1 year before levosimendan (−1.5) and heart rate >70 b.p.m. (−2). Patients with a score less than −1 had a very low probability of response (21.5% free of death or HF event at 1 year) meanwhile those with a score over 1.5 had the better chance of response (68.4% free of death or HF event at 1 year). LEVO‐D score performed well in the ROC analysis. Conclusion: In this large real‐life series of AHF patients treated with levosimendan as destination therapy, we show a significant decrease of heart failure events during the year after the first administration. The simple LEVO‐D Score could be of help when deciding about futile therapy in this population.